Concept and issues in engineering education - Mohd. Ghazali, Mohd. Zulkifli (1995)
This paper presents a background of engineering education in Malaysia; poses several issues and discusses concepts relating to engineering - education in general. The need for a relevant continuing engineering education and an effective Industry-University link is highlighted.